2000
DOI: 10.1017/s0007114500000751
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 677C → T and 1298A → C mutations on plasma homocysteine and 5,10-methylenetetrahydrofolate reductase activity in healthy subjects

Abstract: We have studied the effect of common mutations (677C ! T and 1298A ! C) of the methylenetetrahydrofolate reductase (MTHFR) gene in sixty-six healthy French subjects, aged 27±47 years. Serum folate, vitamin B 12 , and plasma total homocysteine were measured as well as the speci®c activity of MTHFR in lymphocytes. The frequency of subjects homozygous for the 677TT genotype was 18 %, and that of those homozygous for the 1298CC genotype was 12×5 %. The frequency of individuals heterozygous for both mutations was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
85
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 10 publications
6
85
0
3
Order By: Relevance
“…These data corroborate several earlier investigations in the field. 3,19,20,33 As the physical distance of 2.1 kb between the two polymorphisms is short, it is not surprising that recombination events very rarely have been observed. 19,34,35 However, these and our results are in apparent contradiction with those reported in two studies by Isotalo et al 21,36 who found a substantial number of combined MTHFR 677TT/1298AC genotypes in adults (approximately 10% of the study participants), 36 neonates (1.7%) 21 and aborted embryos (1.2%), 21 and 677CT/1298CC and 677TT/1298CC genotypes selectively in aborted embryos (3.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data corroborate several earlier investigations in the field. 3,19,20,33 As the physical distance of 2.1 kb between the two polymorphisms is short, it is not surprising that recombination events very rarely have been observed. 19,34,35 However, these and our results are in apparent contradiction with those reported in two studies by Isotalo et al 21,36 who found a substantial number of combined MTHFR 677TT/1298AC genotypes in adults (approximately 10% of the study participants), 36 neonates (1.7%) 21 and aborted embryos (1.2%), 21 and 677CT/1298CC and 677TT/1298CC genotypes selectively in aborted embryos (3.7%).…”
Section: Discussionmentioning
confidence: 99%
“…3,19 The 1298C allele clearly leads to a decreased enzyme activity, although not to the same extent as the 677T allele. 3,19,20 Individuals who are homozygous for the 1298C allele have about a 40% reduced enzyme activity in vitro, but do not appear to have higher plasma homocysteine levels than controls. 3,19 However, individuals who are compound heterozygous for the 677T and 1298C alleles, which produces a 677CT/1298AC genotype, have a 40 ± 50% reduced MTHFR activity in vitro and a biochemical profile similar to that seen among 677T homozygotes with increased homocysteine levels and decreased folate levels.…”
Section: Introductionmentioning
confidence: 99%
“…While several mutations within it were described, the best-characterized MTHFR gene polymorphisms are the alanine-to-valine C677T (Frosst et al 1995), and the glutamate-to-alanine A1298C (Van der Put et al 1998) missense mutations. While both SNPs induce milder forms of MTHFR deficiency (Frosst et al 1995, Chango et al 2000, the A1298C SNP, located in the enzyme regulatory domain, unlike the C677T SNP which is found within the enzyme catalytic domain, does not result in either a thermolabile protein or increased tHcy (Hanson et al 2001, Friso et al 2002. Interestingly, 677CT/1298AC compound heterozygosity reportedly has similar clinical impact as C677T homozygosity (Chango et al 2000, Chen et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of the MTHFR C677T polymorphism in the general population is about 45% and 15% for heterozygous and homozygous genotypes, respectively. The prevalence of homozygotes for the MTHFR 677TT polymorphism in Europe varies between 5 and 15%; the heterozygous MTHFR C677T genotype presents the highest prevalence in Italy (44%) and the lowest in Norway (28%) (3,4,8,9).The role of MTHFR polymorphisms in VTE is controversial: some authors have shown an association between the MTHFR C677T polymorphism and VTE (10-14), whereas others have proven the contrary (15)(16)(17) …”
mentioning
confidence: 99%